A comparative study of color meaning and preferences for interiors of undergraduate students of different socioeconomic classes from rural and urban communities - Obong, Nicole Carmen D.
ABSTRACT The study aimed to identify the differences in color meaning and preferences of undergraduate students of the University of the Philippines, Diliman. The study used a correlational research design which intended to determine the relationship of color meaning and preferences in relation to community the respondents grew up in and their family's present socioeconomic class. Respondents of this study were selected purposively and a total of 132 respondents were included in the study. Data was gathered using three-part survey and it adopted Guerin and Park's (1995) Integrated Color Palette survey. Results of this study showed no significant differences in color meaning across different communities and different socioeconomic classes. The differences in preferences, however, were significant. Respondents from the rural communities prefer palettes with warm hues, and respondents from urban communities prefer palettes with more neutral hues. Respondents falling under the low socioeconomic class category prefer palettes with warm hues, and more neutral hues were preferred by those falling under the middle income socioeconomic class category. The preferences of high socioeconomic class respondents were more varied maybe because of a more direct influence on changing trends. Further research on the effects of trends and its influences in interior color design preferences is recommended. Also, further research on regional cultural background of respondents may also be effective variables in color preferences and color meanings.